Water-absorbent resin prepared from acrylic acid wastewater as well as preparation method and application of water-absorbent resin

Through the concentration and redox polymerization of acrylic wastewater, combined with biochar and zeolite modification, water-absorbing resin is prepared, which solves the problems of high acrylic wastewater treatment cost and energy waste in the prior art, and achieves efficient utilization and good water absorption performance .

CN119285835AActive Publication Date: 2025-01-10ZHENGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411467134.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-10
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

In the prior art, when treating acrylic wastewater, the incineration method consumes a lot of fuel and is costly. The electrodialysis method requires a lot of electricity and frequent replacement of diaphragms, and the processing speed is slow and there are problems of waste of energy and high operating costs.

Method used

A water-absorbent resin is prepared by using a method that does not require adjustment of the pH value, through the concentration, redox polymerization of acrylic wastewater, combined with biochar and zeolite modification, to simplify the process and improve the wastewater utilization rate.

Benefits of technology

The efficient utilization of acrylic wastewater is achieved, and the water-absorbing resin with good water absorption and fertilizer retention properties is prepared, which reduces production costs and increases the added value of wastewater, solving the problems of energy waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285835A_ABST
    Figure CN119285835A_ABST
Patent Text Reader

Abstract

The invention provides water-absorbent resin prepared from acrylic acid wastewater as well as a preparation method and application of the water-absorbent resin. The preparation method mainly comprises the following steps: firstly, carrying out concentration treatment on acrylic acid wastewater to obtain an acrylic acid concentrated solution; adding an acrylic monomer, a cross-linking agent, an initiator, charcoal and / or zeolite into the acrylic acid concentrated solution, uniformly mixing, carrying out redox polymerization reaction at 60-80 DEG C in a closed environment to form sodium polyacrylate, and drying to obtain the water-absorbent resin. According to the preparation method, the acrylic acid wastewater and the acrylic acid are taken as main raw materials, the water-absorbent resin is prepared by adopting a one-pot method, and the preparation method is simple and low in cost. The invention also provides the water-absorbent resin prepared by the method, the water-absorbent resin has good water retention and fertilizer retention performance, and the additional value of wastewater utilization is effectively improved. The invention also provides an application of the water-absorbent resin in preparation of a water-retaining and / or fertilizer-retaining material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste resource utilization, and in particular to a water-absorbent resin prepared by utilizing acrylic acid wastewater, and a preparation method and application thereof. Background Art

[0002] Acrylic acid wastewater comes from the production of acrylic acid and the manufacturing process of acrylic acid esters and water-soluble resins. It contains a large amount of acrylic acid and its esters. If it is discharged directly into the natural environment without treatment, it will cause serious pollution to water, soil and air. Due to the high concentration and toxicity of acrylic acid wastewater, it is difficult to treat. The main treatment processes in the industry are incineration, electrodialysis or biochemical treatment.

[0003] The existing incineration method usually involves atomizing the waste liquid first, then spraying the atomized waste liquid into a high-temperature furnace from the top, where it is completely vaporized under the action of high temperature to generate harmless carbon dioxide, water and inorganic ash. The main components of acrylic acid wastewater are small molecular organic matter, and it is difficult to carry out concentration pretreatment. The combustion cannot be carried out automatically. The combustion method requires a large amount of fuel, large investment, and high operating costs.

[0004] The existing electrodialysis method mainly adopts the following two methods: one is to circulate acrylic acid wastewater in an electrodialyzer, and separate acrylic acid and other components in the wastewater through a biofilm, so as to achieve the purpose of concentrating acrylic acid. The number of biofilms is calculated according to the wastewater treatment volume corresponding to the membrane area. However, this process requires regular replacement of the biofilm, and the operating cost is high, but it can effectively treat wastewater and recover acrylic acid. Another method is to concentrate a part for acrylic acid recovery, and the other part of the dilute phase can be biochemically treated. However, this method requires a lot of electricity resources. The use of electrodialysis to treat acrylic acid wastewater can realize the recovery and utilization of acrylic acid in wastewater, reducing energy waste. However, this technology has the disadvantages of slow processing speed and large construction area. In addition, the membrane needs to be replaced frequently, which consumes a lot of electricity resources, has high operating costs, and the odor of the wastewater itself is not suitable for this process.

[0005] In order to solve the above problems, CN112745418A discloses a method for preparing low molecular weight sodium polyacrylate using wastewater generated by producing acrylic resin, comprising adjusting the pH value of the wastewater generated by producing acrylic resin to 7.5-8.5 with sodium hydroxide or sodium carbonate, filtering and removing impurities, and concentrating the obtained filtrate by reduced pressure evaporation to obtain a sodium acrylate concentrate; mixing the sodium acrylate concentrate, sodium bisulfite and ammonium persulfate, and performing a polymerization reaction at 60-70° C. to obtain a reaction liquid; and cooling the reaction liquid and adjusting the pH value to 7.0-7.5 to obtain a low molecular weight sodium polyacrylate solution. Although the above patent application utilizes the wastewater generated by the production of acrylic resin to prepare low molecular weight sodium polyacrylate, fully utilizing the acrylic acid and sodium acrylate resources in the wastewater and increasing the added value of the wastewater, it is necessary to adjust the pH value of the wastewater to 7.5-8.5 with sodium hydroxide or sodium carbonate to prevent the subsequent polymerization reaction from failing or causing "explosion", and then concentrate and evaporate it as a raw material for synthesizing sodium polyacrylate, which is a complicated process; and in addition, filtering and impurity removal are also used in the process of the above patent application, mainly to remove some insoluble substances. If they are not removed, the reactor may be blocked, affecting the subsequent reaction and reducing the utilization rate of the wastewater generated by the production of acrylic resin. Summary of the invention

[0006] In view of this, the main purpose of the present invention is to provide a preparation method of a water-absorbent resin prepared by using acrylic acid wastewater. The preparation method uses acrylic acid wastewater and acrylic acid as main raw materials, does not need to adjust the pH value to remove impurities from acrylic acid wastewater, and adopts a one-pot method to prepare the water-absorbent resin. The preparation method is simple and low in cost, and the prepared water-absorbent resin has good water and fertilizer retention properties, which effectively improves the added value of wastewater utilization.

[0007] Specifically, a method for preparing a water-absorbent resin using acrylic acid wastewater comprises the following steps: firstly concentrating the acrylic acid wastewater to obtain an acrylic acid concentrate; adding acrylic acid monomer, a crosslinking agent, an initiator, biochar and / or zeolite to the acrylic acid concentrate, uniformly mixing, and performing a redox polymerization reaction in a closed environment at 60 to 80° C. to form a polymer sodium polyacrylate, drying, and obtaining a water-absorbent resin, wherein the amount of the biochar added is 0 to 8 wt.%, and the amount of the zeolite added is 0 to 3 wt.%. The content of sodium acrylate in the acrylic acid concentrate is 35 to 45%.

[0008] In order to improve the utilization rate of acrylic acid wastewater and ensure the water absorption performance of the absorbent resin, the mass ratio of the acrylic acid monomer to the sodium acrylate in the acrylic acid wastewater is preferably 0.5: 1 to 1.5: 1, the amount of initiator added is preferably 2wt.% to 6wt.% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater, the amount of cross-linking agent added is preferably 1 wt.% to 3wt.% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater, the reaction time is preferably 60 to 360 min, the neutralization degree of the acrylic acid monomer is preferably 50% to 90%, the amount of biochar added is preferably 0 to 8wt.% of the absorbent resin; and the amount of zeolite added is preferably 0 to 3 wt.% of the bioabsorbent resin.

[0009] In order to further improve the water absorption performance of the water-absorbing resin, biochar and zeolite are used to modify it. The amount of biochar added is preferably 2 to 5 wt.% of the water-absorbing resin; the amount of zeolite added is preferably 0.5 to 1.5 wt.% of the raw water-absorbing resin. The acrylic acid wastewater used in the present invention is mainly obtained by removing only some obvious suspended solids from the wastewater discharged from the factory. It is weakly acidic and includes an acrylate monomer product with a content of about 20%. The acrylate monomer product is mainly composed of 13 monomer products such as sodium acrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, and dipentaerythritol hexaacrylate, and sodium acrylate is the main component. Moreover, the acrylic acid wastewater used in the present invention also includes impurities such as dipropylene glycol diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, methanol, ethanol, acetic acid, and acetone.

[0010] Furthermore, the redox polymerization reaction includes: firstly adding acrylic acid monomer to the acrylic acid concentrate, uniformly mixing, then adding the initiator and cross-linking agent, then adding biochar and zeolite, and bubbling N2 at a rate of 20 to 100 mL / min for 3-8 min, then in a closed environment at 60-80°C water bath, gelation occurs for 10-16 h to form a hydrogel, and the hydrogel is sequentially dried, washed, dried twice, and crushed to obtain a water-absorbent resin. There are two main reasons for synthesizing acrylic resin under closed conditions. One is to prevent volatile loss: acrylic acid is volatile, and closed reaction can reduce the loss of raw materials and improve reaction efficiency; the other is to improve product purity: nitrogen is introduced and in a closed system, the stability of the reaction environment can be maintained, moisture, oxygen and other factors in the external air can be prevented from affecting the reaction, and the occurrence of side reactions can be better controlled, thereby improving the purity and quality of the final product.

[0011] The present invention also provides a water-absorbent resin prepared by the above method. Wherein, when the raw material of the water-absorbent resin contains biochar and zeolite, the main component of the water-absorbent resin modified by biochar and / or zeolite is sodium polyacrylate. When the raw material of the water-absorbent resin contains biochar and zeolite, the water-absorbent resin is a water-absorbent resin modified by biochar and / or zeolite, and its main component is sodium polyacrylate modified by biochar and / or zeolite.

[0012] The initiator used in the present invention may be ammonium persulfate, benzoyl peroxide, sodium nitrite, potassium persulfate, etc.; the crosslinking agent used in the present invention may be N'N-methylenebisacrylamide, propylene glycol dimethacrylate, trimethylolpropane triacrylate, etc.

[0013] It has been verified by experiments that the water absorption rate of the water-absorbent resin provided by the present invention for distilled water and 0.9 wt.% NaCl is above 100 g / g and above 30 g / g, respectively, preferably 120-285 g / g and 30-60 g / g; wherein, the water absorption rate of the water-absorbent resin not modified by biochar and / or zeolite for distilled water and 0.9 wt.% NaCl can reach 200 g / g and 37 g / g, and the water-absorbent resin modified by biochar and / or zeolite for distilled water and 0.9 wt.% NaCl can reach 285 g / g and 60 g / g, respectively. Therefore, the water-absorbent resin prepared by the present invention has good water absorption rate, water absorption, soil water retention, recyclable practicality, and fertilizer retention performance. Therefore, the present invention also provides an application of the water-absorbent resin in the preparation of water-retaining and / or fertilizer-retaining materials.

[0014] The present invention also provides a water-retaining slow-release fertilizer, comprising the water-absorbing resin and a fertilizer loaded on the water-absorbing resin. The fertilizer may be a nitrogen fertilizer, a phosphate fertilizer, etc. In this way, the utilization rate of water resources and fertilizers can be improved, environmental problems can be alleviated, new ideas and methods can be provided for the preparation of water-retaining and fertilizer-retaining materials, and basic theoretical guidance can be provided for their application.

[0015] Therefore, the water-absorbing resin synthesized from acrylic acid wastewater in the present invention is used as a water-retaining and fertilizer-retaining material, which can solve the problem of acrylic acid wastewater treatment and make resource utilization. Furthermore, the water absorption rate, water absorption, soil water retention, recyclability and fertilizer retention performance of the water-absorbing resin prepared by the present invention using activated carbon / orthorhombic zeolite modification are further improved. The use of the above-mentioned water-absorbing resin in agriculture not only saves energy, but also explores a new type of water-retaining and fertilizer-retaining material. At the same time, it can also solve the low fertilizer utilization rate and the increasingly serious water shortage problems, and promote the sustainable development of agriculture. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A flow chart of the preparation of the water-absorbent resin provided in Example 1 of the present invention; Figure 2 The figure is a result of the effect of monomers and ratios on the water absorption rate of the water-absorbent resin prepared in Example 1 of the present invention; Figure 3 The figure is a result diagram showing the effect of reaction temperature on the water absorption rate of the water-absorbent resin prepared in Example 1 of the present invention; Figure 4 1 is a kinetic curve diagram of the diffusion of distilled water (a) and 0.9 wt.% NaCl solution (b) in the water-absorbent resin prepared in Example 1 of the present invention; Figure 5 This is a result diagram showing the effect of the amount of initiator on the water absorption rate of the water-absorbent resin prepared in Example 1 of the present invention; Figure 6 The figure is a result of the effect of the amount of cross-linking agent on the water absorption rate of the water-absorbent resin prepared in Example 1 of the present invention; Figure 7 A flow chart for preparing the modified water-absorbent resin provided in Example 2 of the present invention; Figure 8 Result diagram showing the effect of the degree of neutralization of acrylic acid on the water absorption rate of the water-absorbent resin prepared in Example 2 of the present invention; Fig. 9 The effect of the amount of biochar on the water absorption rate of the modified water-absorbent resin prepared in Example 2 of the present invention is shown in the figure; Fig.10 The effect of zeolite dosage on the water absorption rate of the modified water-absorbent resin prepared in Example 2 of the present invention is shown in the figure; Fig.11 The Fourier transform infrared spectra of the unmodified water-absorbing resin and the modified water-absorbing resin prepared under the optimal conditions by Examples 1 and 2 of the present invention, wherein Figures a, b, c, and d are the Fourier transform infrared spectra of biochar, clinoptilolite, modified resin, and unmodified resin, respectively; Fig.12 The thermogravimetric analysis spectra of the unmodified water-absorbent resin and the modified water-absorbent resin prepared under the optimal conditions in Examples 1 and 2 of the present invention; Fig.13 The SEM images of the unmodified water-absorbent resin (a) and the modified water-absorbent resin (b) prepared under the optimal conditions in Examples 1 and 2 of the present invention; Fig.14 The water absorption rate curves of the unmodified water-absorbent resin and the modified water-absorbent resin prepared under the optimal conditions in Examples 1 and 2 of the present invention at different pH values; Fig.15The figures are the recyclability effect diagrams of the unmodified water-absorbent resin and the modified water-absorbent resin prepared under the optimal conditions in Examples 1 and 2 of the present invention in distilled water (a) and 0.9 wt.% NaCl solution (b); Fig.16 The water retention effect diagram of the unmodified water-absorbent resin and the modified water-absorbent resin prepared under the optimal conditions in Examples 1 and 2 of the present invention in soil; Fig.17 The sustained-release behavior curves of the unmodified water-absorbent resin and the modified water-absorbent resin loaded with urea in distilled water prepared under optimal conditions in Examples 1 and 2 of the present invention are shown. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0018] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified.

[0019] In the following embodiments, the amounts of initiator and cross-linking agent are calculated based on the percentage of the total mass of acrylic acid monomer and sodium acrylate in acrylic acid wastewater, the amounts of biochar and zeolite are calculated based on the percentage of the total mass of modified water-absorbent resin, and the neutralization degree of acrylic acid monomer is adjusted by sodium hydroxide.

[0020] The measurement methods of the water absorption rate and the salt water absorption rate in each embodiment are all based on the current industry standards for agricultural and forestry water-retaining agents.

[0021] Example 1 See also Figure 1 The present invention provides a method for preparing a water-absorbent resin using acrylic acid wastewater, comprising the steps of: concentrating the sodium acrylate wastewater to 50% of the initial mass of an acrylic acid concentrate by rotary evaporation, wherein the content of sodium acrylate in the acrylic acid concentrate is about 40%, and using the solution as an experimental raw material. Adding acrylic acid monomer (AA) to the acrylic acid concentrate, mixing evenly, obtaining a monomer mixed solution; adding ammonium persulfate (APS) and N'N-methylenebisacrylamide (MBA) to the monomer mixed solution, bubbling N2 into the reaction system for 5 minutes, sealing the reaction system and placing it in a 60-80°C water bath; after gelation for 12 hours, drying the hydrogel, and crushing to obtain a water-absorbent resin. In this embodiment, the mass ratio of the added acrylic acid monomer to the sodium acrylate in the sodium acrylate wastewater is (0.5-1.5): 1, the neutralization degree of the acrylic acid monomer is 50%-90%, the amount of the initiator APS is 2-6 wt.%, and the amount of the crosslinking agent MBA is 1.0-3.0 wt.%.

[0022] In the redox polymerization process, the initiator APS is reduced to generate sulfate ion radicals (Formula 1), which can attract hydrogen from the hydroxyl group of biochar to form alkoxy groups or attract AA molecules to form AA radicals (Formulas 2 and 3). The biochar or AA molecules near the reaction site become free radical acceptors (Formulas 2 and 4). After accepting the free radicals, they become the next free radical donors of the adjacent molecules to initiate the chain growth reaction. The chain growth of sodium acrylate may be terminated by combining two polyacrylic acid (PAA) chains or connecting with biochar (Formula 5). During the chain growth process, the vinyl group at the end of MBA, which acts as a crosslinker, can react synchronously with the polymer PAA chain to form a three-dimensional network structure.

[0023] It can be seen that in the process of preparing the water-absorbent resin using acrylic acid wastewater, the amount of each raw material, the degree of AA neutralization, the reaction temperature, the reaction time, etc. all have an impact on the synthesis and performance of the water-absorbent resin. The water absorption performance of the water-absorbent resin synthesized using the preparation method provided in this embodiment is further explained below with respect to the above-mentioned influencing factors.

[0024] 1.1 Effect of the mass ratio of acrylic acid monomer to sodium acrylate in acrylic acid wastewater on the performance of water-absorbent resin The reaction parameters are as follows: the mass ratio of acrylic acid monomer to sodium acrylate in acrylic acid wastewater (hereinafter referred to as "monomer ratio") is 0.5:1, 0.75:1, 1:1, 1.25:1, 1.5:1, respectively; the reaction temperature is 60°C; the amount of initiator APS is 5wt.%, the amount of crosslinker MBA is 1wt.%, and the reaction time is 180 min; the effect of monomer ratio on the water absorption rate of water-absorbent resin is shown in the following figure. Figure 2 shown.

[0025] Figure 2 It shows that when the monomer ratio is changed, the water absorption rate of the water-absorbent resin increases continuously, and then decreases slightly after reaching the maximum value. This is because when the monomer concentration is too low, the polymerization rate is relatively slow, the molecular chain of the product is too short, and only a few active groups can be adsorbed. When the monomer concentration is too high, the polymerization rate is too fast, and the reaction time is greatly shortened, resulting in the inability of the monomers to fully cross-link under the action of the cross-linking agent to form a three-dimensional network structure, and the water absorption rate is greatly reduced. Therefore, the monomer ratio is preferably 0.9:1 to 1.25:1, and more preferably 1:1 to 1.25:1, and when the monomer ratio is 1:1, the water absorption rate of the synthesized water-absorbent resin is the highest, and the water absorption rates in distilled water and 0.9wt.% NaCl solution reach 185 g / g and 35 g / g, respectively.

[0026] 1.2 Effect of reaction temperature on the performance of water-absorbent resin The reaction parameters are: monomer ratio is 1:1, reaction temperatures are 60℃, 65℃, 70℃, 75℃, 80℃, initiator dosage is 5wt.%, crosslinker dosage is 1wt.%, reaction time is 180 min. Figure 3 shown.

[0027] Figure 3 It is shown that the water absorption rate of the water-absorbent resin increases with the increase of reaction temperature until it reaches the maximum value at 70°C. When the reaction temperature is too low, the reaction rate is slow, and then decreases with further increase of temperature. This is mainly because the polymerization reaction includes the self-polymerization and grafting reaction of acrylic acid, and the grafting rate affects the water absorption performance of the water-absorbent resin. Higher temperature contributes to the self-polymerization of acrylic acid, thereby reducing the grafting rate. Therefore, the reaction temperature is preferably 65-75°C, the optimal temperature is 70°C, and the water absorption rate of the water-absorbent resin synthesized at this optimal temperature in distilled water and 0.9 wt.% NaCl solution reaches 191 g / g and 36 g / g, respectively.

[0028] 1.3 Effect of reaction time on the performance of water-absorbent resin The reaction parameters are: monomer ratio of 1:1, reaction temperature of 70°C, reaction time of 0-1000 min, initiator dosage of 5wt.%, and crosslinker dosage of 1wt.%. The effect of reaction time on the water absorption rate of water-absorbent resin is as follows: Figure 4 shown.

[0029] Figure 4 It is shown that the water absorption rate increases rapidly in the initial stage and then increases slowly in distilled water (a) and 0.9 wt.% NaCl solution (b) to reach a balanced state. This result may be related to the change in the osmotic pressure difference during the swelling process. Due to the electrostatic repulsion between the hydrophilic groups and the anionic groups in the resin structure, the osmotic pressure difference is very high, water molecules can easily enter the network of the superabsorbent, and the swelling rate increases rapidly. However, as more water molecules join the network, the osmotic pressure difference gradually weakens, the swelling rate becomes smaller, and finally reaches a balanced state. Therefore, the reaction time is preferably 60 to 360 min, and more preferably 120 to 240 min.

[0030] 1.4 Effect of initiator dosage on the performance of water-absorbent resin The reaction parameters are: monomer ratio is 1:1, reaction temperature is 70℃, the amount of initiator APS is 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, the amount of crosslinker is 1 wt.%, and the reaction time is 180 min. The effect of initiator APS on the water absorption rate of water-absorbent resin is shown in Figure 2. Figure 5 shown.

[0031] from Figure 5 It can be seen that the water absorption rate of the water-absorbent resin increases with the increase of the amount of APS, and reaches the maximum value at 4 wt.% APS, and the water absorption rate in distilled water is 196 g / g, and the water absorption rate in 0.9 wt.% NaCl solution is 37 g / g, which is mainly because more free radicals and more active sites are generated on the main chain of sodium acrylate. However, further increasing the amount of APS will lead to a decrease in absorbency, because the large amount of free radicals generated by excessive initiator will shorten the length of the grafted chain, thereby affecting the absorbency. Therefore, the amount of initiator is preferably 3 wt% to 5 wt%.

[0032] 1.5 Effect of crosslinking agent dosage on the performance of water-absorbent resin The reaction parameters are as follows: monomer ratio is 1:1, reaction temperature is 70℃, initiator APS dosage is 4 wt.%, cross-linker dosage is 1.0 wt.%, 1.5 wt.%, 2.0 wt.%, 2.5 wt.%, 3.0 wt.%, reaction time is 180 min. The effect of cross-linker MBA on the water absorption rate of absorbent resin is shown in Figure 2. Figure 6 shown.

[0033] from Figure 6 It can be seen that the water absorption rate of the water-absorbent resin increases with the increase of the amount of crosslinking agent. When the mass fraction of the crosslinking agent is 2.0 wt.%, the water absorption rate of the water-absorbent resin is the largest, and the water absorption rates in distilled water and 0.9wt.% NaCl solution are 200 g / g and 35 g / g, respectively. The amount of crosslinking agent is directly related to the crosslinking density, which affects the formation of the polymer network and the mechanical strength. Obviously, higher crosslinking agent levels produce more crosslinking, which also leads to the formation of additional networks, which will reduce the available free volume inside the polymer, thereby reducing the water absorption rate. In addition, insufficient crosslinking agent MBA will reduce the crosslinking density, resulting in an increase in soluble matter, thereby reducing the water absorption rate. Therefore, the amount of crosslinking agent is preferably 1.5wt% to 2.5 wt%.

[0034] Therefore, the optimal synthesis conditions of the water-absorbent resin provided in this embodiment are: monomer ratio of 1:1, acrylic acid neutralization degree of 70%, reaction temperature of 70°C, reaction time of 180 min, initiator APS dosage of 4 wt.%, crosslinker dosage of 2.0 wt.%.

[0035] Example 2 See also Figure 7, the embodiment of the present invention provides a method for preparing a modified water-absorbent resin using acrylic acid wastewater, which is basically the same as the method for preparing a water-absorbent resin using acrylic acid wastewater provided in Example 1, the main difference being that: in this embodiment, after adding APS, sodium bisulfite and MBA to the monomer mixed solution, before N2 is bubbled into the reaction system, biochar and / or zeolite are added, and other method steps and parameters are the same, thereby obtaining a water-absorbent resin modified by biochar and / or zeolite. Among them, in this embodiment, the neutralization degree of acrylic acid AA is 50% to 90%, and the amount of biochar is 0 wt.% to 8 wt.% of the modified water-absorbent resin; the zeolite is clinoptilolite, and its amount is 0 wt.% to 3 wt.% of the modified water-absorbent resin.

[0036] Biochar and zeolite are modified materials for the water-absorbent resin provided in Example 1. The amount of biochar and zeolite used has an important influence on the modified water-absorbent resin obtained in this example, which is further described in detail below.

[0037] 2.1 Effect of AA neutralization degree on the performance of water-absorbent resin The reaction parameters are: monomer ratio is 1:1, AA neutralization degree is 50%, 60%, 70%, 80%, 90%, reaction temperature is 60℃, initiator APS dosage is 5wt.%, crosslinker MBA dosage is 1wt.%, reaction time is 180 min; the effect of AA neutralization degree on the water absorption rate of absorbent resin is shown in the following figure. Figure 8 shown.

[0038] from Figure 8 It can be clearly seen that the AA neutralization degree has a significant effect on the water absorption capacity of the water-absorbent resin. When the AA neutralization degree increases from 50% to 70%, the water absorption of the synthesized water-absorbent resin increases significantly. This observation can be explained by the increase in charge density, which leads to an increase in the electrostatic repulsion of the COO− groups in the polymer matrix. As a result, the resin network becomes larger, and the absorption rate increases from 136 to 279 g / g in distilled water and from 37 to 56 g / g in 0.9 wt.% NaCl solution. At higher neutralization degrees greater than 70%, the water absorption capacity decreases, which may be caused by the increase in chain rigidity and the condensation of counterions on the polyions. Therefore, the AA neutralization degree is preferably 60% to 90%, and more preferably 65% ​​to 80%.

[0039] 2.2 Effect of biochar dosage on the performance of water-absorbent resin The reaction parameters are as follows: monomer ratio of 1:1, AA neutralization degree of 70%, reaction temperature of 70°C, initiator APS dosage of 4 wt.%, cross-linker dosage of 2.0 wt.%, reaction time of 180 min, biochar dosage of 0, 2, 4, 6, 8 wt.%, zeolite dosage of 2 wt.%. The effect of biochar dosage on the water absorption rate of biochar / zeolite modified water-absorbing resin is shown in Figure 2. Fig. 9 shown.

[0040] from Fig. 9 It can be clearly seen that with the increase in the amount of biochar, the number of active groups such as carboxyl and hydroxyl in the reaction system increases rapidly, so that the acrylic monomer has more opportunities to undergo graft polymerization reaction with biochar, and the water absorption rate of the resin is greatly improved. If the amount of biochar continues to increase, too much biochar cannot react completely with the acrylic monomer, but is physically mixed into the structure of the resin, which is equivalent to introducing other impurities, destroying the original three-dimensional network structure, and greatly reducing the water absorption rate of the modified water-absorbent resin. In summary, the amount of biochar is preferably selected to be 2-5 wt.%, and when the amount of biochar is 4 wt.%, the water absorption rate of the modified water-absorbent resin in distilled water and 0.9wt% NaCl solution reaches the highest, which is 281 g / g and 57 g / g, respectively.

[0041] 2.3 Effect of zeolite dosage on the performance of water-absorbent resin The reaction parameters are as follows: monomer ratio of 1:1, AA neutralization degree of 70%, reaction temperature of 70°C, initiator APS dosage of 4wt.%, crosslinker dosage of 2.0wt.%, reaction time of 180 min, biochar dosage of 4wt.%, zeolite dosage of 0.5-3wt.%. The effect of zeolite dosage on the water absorption rate of biochar / zeolite modified water-absorbing resin is shown in Figure 2. Fig.10 shown.

[0042] Zeolite itself has a suitable pore diameter and a large specific surface area, and has good adsorption performance. Fig.10 It can be seen that with the addition of clinoptilolite, the water absorption performance of the modified water-absorbent resin is significantly improved, and the addition of a small amount of clinoptilolite can improve the water absorption performance. At the same time, the negative charge on the surface of clinoptilolite will repel the carboxyl groups in the modified resin, promoting the expansion of the gel network. However, too much clinoptilolite will cause incomplete cross-linking of some polymer networks, and will also reduce the number of hydrophilic groups contained in the unit volume of polymer, thereby reducing the water absorption capacity of the resin. Taking all factors into consideration, the dosage of zeolite is preferably 0.5-1.5 wt.%, and when the dosage of zeolite is 1 wt.%, the water absorption rate of the modified water-absorbent resin in distilled water and 0.9wt% NaCl solution reaches the highest value, 284 g / g and 59 g / g, respectively.

[0043] Therefore, the optimal synthesis conditions for synthesizing the biochar / zeolite modified water-absorbing resin in this embodiment are: monomer ratio of 1:1, acrylic acid neutralization degree of 70%, reaction temperature of 70 ° C, reaction time of 180 min, initiator APS dosage of 4 wt.%, cross-linker dosage of 2.0 wt.%, biochar dosage of 4 wt.%, zeolite dosage of 1 wt.%.

[0044] Structural characterization The water-absorbent resin synthesized under the optimal conditions in Example 1 (hereinafter referred to as "unmodified resin") and the water-absorbent resin modified with biochar zeolite synthesized under the optimal conditions in Example 2 (hereinafter referred to as "modified resin") were characterized by infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy analysis.

[0045] 3.1 Infrared spectroscopy analysis Fig.11 The infrared spectra shown in the figure show that in the spectrum of biochar (a), the 3400 cm −1 The broad peak at 2900 cm −1 Attributed to CH, 1571 cm -1 The peak at 1384 cm is the stretching vibration absorption peak of the carbonyl conjugated double bond (C=O); -1 The vibration peaks of hydroxyl (-OH) are at 1183 and 1037 cm -1 The peak at 1008 cm is the stretching vibration peak of CO in the ether and alcohol structures in biochar. Spectrum of clinoptilolite (b), 1008 cm -1 The absorption peak is the Si-O (Si) bond.

[0046] The infrared spectra of the unmodified resin (d) and the modified resin (c) show that the -1 A strong absorption peak appeared at 3200-3500 cm-1, which is the overlapping stretching vibration peak of the carbonyl group (C=O) in acrylic acid. -1 Compared with SAP, BC-SAP has a broad absorption peak of OH at 1637 cm -1 The stretching vibration peak of the aromatic conjugated double bond (C=C) of biochar appeared at 1365 cm -1 The hydroxyl (-OH) vibration peak in biochar appeared at 1190 cm -1 and 1053 cm -1 At 988 cm -1 There is a stretching vibration peak of Si-O (Si) group at 1008 cm -1The peak at was shifted, which proved that clinoptilolite participated in the polymerization reaction.

[0047] 3.2 Thermogravimetric analysis from Fig.12 The thermogravimetric curves of the unmodified and modified resins shown in the figure show that the decomposition of the unmodified and modified resins is divided into three steps. In the first step, the resin is heated from room temperature to 100 ° C, and the mass loss is about 4%. This step is mainly caused by the evaporation of free water in the resin. In the second step, from 100 to 420 ° C, the mass losses of the unmodified and modified resins are 30.72% and 31.68%, respectively. This step is caused by the degradation of the cross-linked network structure of the resin and the decomposition of the polymer chain. In the third step, from 420 ° C to 480 ° C, 22.10% and 24.93% of the mass are lost rapidly during this process. These losses are caused by the evaporation of volatile components in the sample and the carbonization of the polymer chain. When the temperature is higher than 480 ° C, the mass loss rate is very fast, and the mass loss of the unmodified and modified resins is 24.99% and 21.37%, respectively. Most of the resin is converted into carbon and completely loses its performance. As the temperature increases further, the mass loss of the two resins tends to slow down. Comparing the thermogravimetric curves of unmodified and modified resins, the two curves have similar trends, and the final residue mass differs by 4.85%, which shows that the addition of biochar and clinoptilolite slightly improves the stability of the super absorbent resin. The reason may be that at high temperatures, acrylic acid polymers are more stable than biochar and decompose more thoroughly at high temperatures, so the residue mass of the modified resin is lower than that of the unmodified resin. In general, both absorbent resins have good thermal stability, and the effect of temperature on the resin structure can be ignored when used in agriculture.

[0048] 3.3 Scanning electron microscopy analysis SEM images of the appearance of unmodified and modified resins in the dry state are shown in Fig.13 As shown. The dried unmodified resin (a) has a rigid structure and a smooth surface, and the surface is porous. The porous structure allows water molecules to quickly enter the resin, which helps to quickly reach swelling equilibrium. The smooth surface can help to slow down the release rate of water molecules to a certain extent. This observation shows that the unmodified resin can absorb and retain a large amount of water without losing its structural integrity, which is confirmed by the results of scanning electron microscopy analysis. The SEM image of the appearance morphology of the modified resin (b) was observed, and the surface of the product had a large number of wrinkles and an uneven shape; this shows that the synthesized modified resin has a larger specific surface area, which is conducive to water molecules to penetrate into the polymer network more easily and faster, and can absorb more water molecules. In addition, these interconnected pores can delay the dissolution of urea in the swelling medium and improve the slow-release behavior of the resin.

[0049] Performance Verification 4.1 Water absorption By observing the unmodified and modified resins of the products in dry state Fig.13 As shown in the SEM image, the unmodified resin can absorb and retain a large amount of water without losing its structural integrity. The surface of the modified water-absorbing resin has a large number of wrinkles and an uneven shape, with a large specific surface area, which is conducive to water molecules to penetrate into the polymer network more easily and quickly, and can absorb more water molecules at the same time.

[0050] (2) Effect of pH value on water absorption rate The water absorption rate of the unmodified resin and modified resin synthesized under the best conditions was tested in distilled water with a pH value of 2 to 12, where the pH value was adjusted with hydrochloric acid and sodium hydroxide, respectively. The results of the effect of the pH value of distilled water on the unmodified and modified resins are shown in Fig.14 shown.

[0051] Fig.14 The results show that the water absorption of unmodified resin and modified resin show similar change trends in a wide pH range, with a sharp increase in the pH range of 3-7 and a significant decrease in the pH range of 9-12. Under acidic conditions, the water absorption rate is small and the water absorption is poor. Most of the -COO- groups are oxidized and converted into -COOH groups, the repulsion between anions is weakened, and the three-dimensional network structure shows a shrinking behavior. On the other hand, due to the higher protonation and increased crosslinking degree of the network, the hydrogen bond interaction is enhanced, resulting in a decrease in the water absorption rate. With the increase of pH value, the negative effect of hydrogen ions on the electrostatic repulsion of carboxylate anions is reduced, and the hydrogen bond interaction is limited. Therefore, the network structure of unmodified resin and modified resin is further expanded, the water absorption is enhanced, the absorption rate increases, and reaches its maximum value of 190 g / g and 300 g / g respectively at pH 7. However, at higher pH values ​​of pH>9, due to the excess Na + The shielding effect of ions reduces water absorption, prevents repulsive electrostatic interactions, and reduces water absorption. On the other hand, the water absorption rate of the modified resin is significantly higher than that of the unmodified resin. The main reason is that the addition of biochar and clinoptilolite leads to the addition of a large number of active groups such as hydroxyl and carboxyl groups in the system. This shows that the addition of biochar and clinoptilolite has greatly improved the network structure inside the resin, thereby improving the water absorption and water retention performance. Therefore, the above unmodified resin and modified resin are preferably used in distilled water with a pH value of 6 to 10, and the water absorption rate is above 140 g / g.

[0052] (3) Recyclability The recyclability of water-absorbent resin products is the ability to absorb water after multiple saturated water absorption and thorough drying, which determines the service life of water-absorbent resin products. In order to examine the recyclability of the water-absorbent resin prepared by the embodiment of the present invention, 1.00 g of the unmodified resin and the modified resin were taken respectively, and the liquid absorption cycle test was carried out 5 times to measure the water absorption rate. The results are as follows: Fig.15 shown.

[0053] from Fig.15 It can be seen that after five cycles, the water absorption rates of the unmodified resin (a) and the modified resin (b) in distilled water were 107 g / g and 204 g / g, respectively, which were about 53.5% and 72.86% of their initial water absorption capacity (based on the maximum water absorption rate in distilled water); the water absorption rates of the unmodified resin and the modified resin in 0.9wt.%NaCl solution were 28 g / g and 45 g / g, respectively, which were about 70% and 75% of their initial water absorption capacity (based on the maximum water absorption rate in 0.9 wt.%NaCl solution). These results show that biochar and zeolite have improved the three-dimensional network structure of the water-absorbing resin and improved its recyclability.

[0054] (4) Soil water retention performance The water retention of unmodified and modified resin samples in soil was determined to study the water retention properties of the two water-absorbing resins within their polymeric network structure after being placed for 30 days. For this purpose, the soil was initially dried in an oven at 80°C for two days and sieved through a 10-mesh nylon sieve. Then, 1.00 g of the prepared unmodified and modified resin samples were mixed with 10 g of dry soil in a plastic beaker, and distilled water was added to the mixture of resin sample and soil. Subsequently, the beaker was weighed and placed at room temperature. At the same time, a blank test without the addition of resin was carried out (the beaker contained the same soil without resin). The beaker was weighed every 2 days for 30 consecutive days, and the results are shown in Figure 2. Fig.16 shown.

[0055] Fig.16 The water retention behavior of soil containing unmodified resin, modified resin and no added resin for 30 days is shown. The results show that the water evaporation rate of soil with added resin is significantly lower than that of soil without addition, and the soil with unmodified and modified resins maintained 29% and 38% of the initial water content after 30 days. These results show that the water evaporation of soil using the absorbent resin provided by the embodiment of the present invention is significantly lower than the water evaporation of blank soil, and the water retention of modified resin in soil is significantly higher than that of unmodified resin.

[0056] (5) Fertilizer retention performance Test method: Accurately weigh 1.00 g of unmodified resin and modified resin respectively and place them in 5 g / L urea solution for 24 h. Place the resins that have reached swelling equilibrium in an oven and dry them to constant weight. Accurately weigh the resin weight and calculate the urea loading mass. Immerse the urea-loaded resins in 400 mL of distilled water respectively, carefully take out 2 mL of solution every 1 h, obtain the urea amount by ultraviolet spectrophotometry, and immediately add the same amount of fresh distilled water to the culture medium for the next test. Determine the urea content according to GB / T23348-2009, and the results are as follows: Fig.17 shown.

[0057] Fig.17 The results show that the urea release rates of the unmodified and modified resin-loaded urea in 10 h were 75% and 57%, respectively, indicating that the network of the water-absorbent resin is tight enough to keep the urea molecules inside. Therefore, water and urea molecules are inhibited, their release is delayed, and the fertilizer retention performance of the modified water-absorbent resin is higher than that of the unmodified water-absorbent resin over a longer period of time.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A method for preparing a water-absorbent resin using acrylic acid wastewater, comprising the steps of: firstly concentrating the acrylic acid wastewater to obtain an acrylic acid concentrate; adding acrylic acid monomer, a crosslinking agent, an initiator, biochar and / or zeolite to the acrylic acid concentrate, uniformly mixing, and performing a redox polymerization reaction in a closed environment at 60 to 80° C. to form sodium polyacrylate, and drying to obtain a water-absorbent resin; Preferably, the content of sodium acrylate in the acrylic acid concentrate is 35-45%.

2. The method according to claim 1, characterized in that The mass ratio of the acrylic acid monomer to the sodium acrylate in the acrylic acid wastewater is 0.5: 1 to 1.5: 1, the reaction time is 60 to 360 min, the amount of the initiator added is 2 wt% to 6 wt% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater, and the amount of the crosslinking agent added is 1 wt.% to 3 wt.% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater.

3. The method according to claim 2, characterized in that The mass ratio of the acrylic acid monomer to the sodium acrylate in the acrylic acid wastewater is 0.9: 1 to 1.25: 1, the reaction temperature is 65 to 75° C., the reaction time is 120 to 240 min, the amount of the initiator added is 3 wt% to 5 wt% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater, and the amount of the cross-linking agent added is 1.5 wt.% to 2.5 wt.% of the total mass of the acrylic acid monomer and the sodium acrylate in the acrylic acid wastewater; Preferably, the mass ratio of the acrylic acid monomer to the sodium acrylate in the acrylic acid wastewater is 1: 1 to 1.25: 1, and the reaction time is 120 to 240 min.

4. The method according to claim 3, characterized in that The neutralization degree of the acrylic acid monomer is 50% to 90%; Preferably, the neutralization degree of the acrylic acid monomer is 65% to 80%.

5. The method according to any one of claims 1 to 4, characterized in that: The amount of biochar added is 0-8wt.%; Preferably, the amount of biochar added is 2 to 5 wt.%.

6. The method according to claim 5, characterized in that The amount of zeolite added is 0 to 3 wt.%; Preferably, the added amount of the zeolite is 0.5-1.5 wt.%.

7. The method according to claim 6, characterized in that The initiator is ammonium persulfate, benzoyl peroxide, sodium nitrite or potassium persulfate; the crosslinking agent is N'N-methylenebisacrylamide, propylene glycol dimethacrylate or trimethylolpropane triacrylate.

8. The water-absorbent resin prepared by the method according to any one of claims 1 to 7; Preferably, the main component of the water-absorbing resin is sodium polyacrylate; Preferably, the main component of the water-absorbing resin is biochar and / or zeolite-modified sodium polyacrylate.

9. Use of the water-absorbing resin according to claim 8 in the preparation of water-retaining and / or fertilizer-retaining materials.

10. A water-retaining slow-release fertilizer comprising the water-absorbent resin according to claim 8 and a fertilizer loaded on the water-absorbent resin.

Citation Information

Patent Citations

  • Method for preparing polyacrylic acid dispersing agents by adopting acrylic acid waste water as raw material

    CN102225976A

  • Preparation technology of water-retention slow-release fertilizer

    CN105693354A

  • Treatment method of (meth)acrylic acid wastewater

    CN110746527A

  • Treatment and resource utilization method of (methyl) acrylic acid wastewater

    CN111253525A

  • Preparation method of high molecular weight sodium polyacrylate

    CN116355115A